Description of two synanthropic silverfish (Insecta: Zygentoma), Ctenolepisma longicaudatum (Escherich, 1905) and Ctenolepisma rothschildi (Silvestri, 1907), from Kerala, India - Raphel, Sheeba; Jose, Joyce (Zootaxa, 2025)
Two silverfish species, Ctenolepisma longicaudatum Escherich, 1905 and Ctenolepisma rothschildi Silvestri, 1907 (Insecta: Zygentoma: Lepismatidae), are reported for the first time from Kerala, India, with the report of C. rothschildi being the first for India. The report presents morphological, meristic and molecular details of the specimens and compares them with reports of the species from other parts of the world. The paper also discusses the presence of distinct populations in C. longicaudatum and advises further studies.